A multivariate analysis of highway infrastructure and economic growth in the local economies in the Philippines - Beloy, Mirrasol M.; Casas, Krisha Angela P.
Infrastructure development is a widely accepted catalyst for economic growth, yet the nature and direction of its impact can vary across regions and contexts. This study investigates the dynamic and causal relationships between road infrastructure-proxied by road length-and sis socioeconomic variables: economic growth, exports, employment, education, electricity access, and motor vehicle registration across 16 Philippine regions from 2005 to 2023. Moving beyond traditional growth theories, the analysis is grounded in Keynesian demand theory and Frischmann's framework on infrastructure as a commons. Using a combination of Pooled Mean Group (PMG) estimation, Panel Vector Autoregression (PVAR), Granger causality tests, Impulse Response Functions (IRFs), and Forecast Error Variance Decomposition (FEVD), this study uncovers both long and short-term interdependencies. Findings reveal significant long-run positive effects of road infrastructure on exports, economic growth, and vehicle registrations, while showing a negative association with education-suggesting either resource misallocation or limitations in data proxies. Short-run dynamics demonstrate unidirectional causality from employment to infrastructure and from education to economic growth. IRFs show infrastructure shocks initially impact employment, electricity, and education, though these effects often dissipate. FEVD results suggest most short- to medium-term variability is self-explanatory within each variable, emphasizing sector specific resilience. The results reveal the importance of region-specific infrastructure planning and reveal that economic returns from road investment are not uniformly distributed. Policymakers are urged to adopt complementary and targeted strategies to ensure inclusive growth and sectoral stability during and after infrastructure implementation. Ultimately, this study highlights the nuanced role of highways in fostering equitable regional development in the Philippines.